Analisis Gaya Belajar Siswa VII-J SMPN 1 Grogol Untuk Pengembangan Media Animasi Berbasis Etnosains - Lidiya Fatmaningsih; Atika Anggraini (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
The purpose of this study is to analyze the learning styles of seventh-grade students (Class VII-J) at SMPN 1 Grogol as a basis for developing ethnoscience-based animation media in science learning. This aim is based on the importance of understanding students’ learning characteristics so that the developed learning media can meet their needs and preferences. The research method used is a descriptive quantitative method with 31 students from Class VII-J of SMPN 1 Grogol as the subjects. Data were collected through a learning style questionnaire to identify students’ learning tendencies and interviews with science teachers to obtain supporting information regarding the learning process and student characteristics. The results of the study show that the majority of students have a visual learning style (52%), followed by auditory (13%), kinesthetic (13%), visual-kinesthetic combination (3%), and visual-auditory combination (19%). These findings indicate that most students find it easier to understand the material through visual presentations such as images, videos, and animations. Therefore, the results of this study can serve as a foundation for designing ethnoscience-based animation media that are not only visually appealing but also connect science concepts with local wisdom in the students’ surroundings. Thus, the developed media are expected to enhance student engagement and understanding in science learning.